A STUDY ON ENGLISH TEACHERSâ TEACHING APPROACHES, METHODS, AND TECHNIQUES AT A STATE SENIOR HIGH SCHOOL IN ENREKANG, INDONESIA - Samad, Ita Sarmita (Jurnal Bahasa Lingua Scientia, 2016)
This research was aimed at identifying the approaches, methods and techniques used by the English teachers at a state senior high school in Enrekang, Indonesia in teaching English as a foreign language. Furthermore, the consistency of the approaches, methods, and techniques is also identifed. This research applied explorative qualitative research design. The subjects were all of the English teachers in that school. They were chosen through purpossive sampling technique. They were interviewed and observed to get data regarding their teaching approach, method, and technique. Their lesson plan were copied to gain supporting data. Based on fndings and discussion, the approaches used by teacher 1 were communicative and behaviorism approach. Teacher 2 applied systemic functional linguistic and constructivism/ cognitivism. Most of the techniques used by teacher 1 reï¬ected behaviorism approach or principles of grammar translation method while the techniques used by teacher 2 reï¬ected both of behaviorism and constructivism. In the case of the consistency, the English teachers still showed a considerable inconsistency. Yet, comparing with teacher 1, teacher 2 was more consistent. It is concluded that the two English teachers still need further upgrading regarding approaches, methods, and techniques of teaching English as a foreign language.